2022
DOI: 10.1111/jfpp.16883
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines in fish: Prevention and reduction

Abstract: High-quality proteins, vital vitamins, minerals, and essential fatty acids may be obtained from fish and fish products. Fish decomposition and the generation of toxicants such as biogenic amines may counteract the benefits of fish consumption on human health, such as protection against coronary heart disease and some cancers.Annually, histamine consumption is recognized as the cause of numerous cases of food poisoning. Even small or moderate doses of histamine or tyramine-containing fish might cause food sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…The prevention and reduction of biogenic amines in fermented products involve both conventional and modern methods. Conventional methods include maintaining proper sanitary conditions, food handling practices throughout food processing, and temperature control during storage to inhibit the bacteria with amino acid decarboxylase activity [ 11 , 42 , 87 ]. Moreover, several studies have indicated that addition of certain food additives or chemicals can help prevent the formation of BAs in fermented foods [ 14 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention and reduction of biogenic amines in fermented products involve both conventional and modern methods. Conventional methods include maintaining proper sanitary conditions, food handling practices throughout food processing, and temperature control during storage to inhibit the bacteria with amino acid decarboxylase activity [ 11 , 42 , 87 ]. Moreover, several studies have indicated that addition of certain food additives or chemicals can help prevent the formation of BAs in fermented foods [ 14 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies have indicated that addition of certain food additives or chemicals can help prevent the formation of BAs in fermented foods [ 14 , 19 ]. For example clove oil, sodium chloride, or a combination of both has been shown to delay and slow down the production of biogenic amines in fish muscle broth [ 87 ]. Other spices, such as garlic, have also been found to have inhibitory effects on BA production in certain fermented fish products [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hygienic Handling and Processing: Ensuring hygienic conditions during seafood processing and handling minimizes contamination with BA-producing bacteria. Good manufacturing practices (GMP) and hazard analysis and critical control points (HACCP) systems are essential tools in this regard (Abuhlega & Ali, 2022).…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…Histamine is a biogenic amine responsible for several allergic and inflammatory phenomena (Oktariani et al, 2022;Bose et al, 2023). It is formed as a result of the enzymatic activity of histidine decarboxylase produced by some bacteria, such as Morganella morganii, Raoultella ornithinolytica, Raoultella planticola, Proteus vulgaris, Proteus mirabilis, Klebsiella sp., Enterobacter cloacae, Enterobacter aerogenes, Citrobacter freundi, Serratia liquefaciens, and Serratia fonticola (Tao et al, 2022;Ginigaddarage et al, 2023;Rachmawati et al, 2023), which is accentuated by poor storage conditions (Emborg and Dalgaard, 2008;Abuhlega and Ali, 2022). This leads to the decarboxylation of L-histidine, which is naturally present in the flesh of many species of fish (García-Ruiz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%